Untapped potential: How the G20 can strengthen global governance - Robert Benson; Michael Zürn (South African Journal of International Affairs, 2019)
The G20 has two distinctive features that make it a unique forum in global politics. First, it is one of the few existing global platforms where different international institutions and regional organisations can coordinate across a vast array of issue areas and emergent policy fields. Second, it is an institution that brings together heads of government which control roughly 80% of world GDP. Despite these features, the G20 lacks constitutive authority of its own, bound by a consensus principle which sharply delimits its scope of action. Notwithstanding its circumspect authority, no recent international body has garnered more attention from transnational civil society groups and advocacy networks than the G20. Most of this attention is critical and points to legitimacy problems. We argue that these legitimacy problems derive from a perception of untapped potential and undue privilege for great powers. Against this backdrop, we submit that a more active and institutionalised forum – with clear decision-making procedures for exercising authority – could help mitigate resistance and contribute to a more legitimate global governance system overall.
Keywords: 330; G20; global governance; meta-governance; informality; reform